Challenges and Strategies for Improving Financial Management Accountability in Thailand: Insights from Islamic Values - Putriyani Azhara Siregar; Rahmayati Rahmayati (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to analyze the main challenges and strategies in improving financial management accountability at Muslimeen Suksa Islamic Private School in Thailand. The research employs a qualitative case study approach. Primary data were obtained through semi-structured interviews with the principal as the person in charge of financial management and classroom teachers involved in budget implementation, supported by observation and document analysis. Data were analyzed through data reduction, data display, and conclusion drawing, while validity was ensured through source and method triangulation. The findings indicate that although financial management functions such as planning, implementation, recording, and reporting have been carried out, accountability has not been fully optimized due to limited human resource competence, weak internal control mechanisms, dependence on government funding, and limited digital financial systems. Accountability is reflected in documented financial reports and conformity between budget plans and realization; however, transparency and digital documentation still require strengthening. Therefore, integrated strategies including digitalization, capacity building, internal supervision, and standardized reporting are needed to enhance sustainable financial accountability. These findings affirm that strengthening institutional accountability is essential to ensure transparency, efficiency, and long-term sustainability of Islamic educational institutions.